Oregano essential oils: Antimicrobial activity and its application to films based on cornstarch and glycerol - Córsico, Francisco Armando (2014)
This trend has led to research on the development of new biodegradable packaging materials from natural polymers also suggests that several materials may be incorporated into edible films and have influence on the mechanical, protective and sensory properties. The objective of this work was to characterize oregano essential oils and incorporated edible films made with cornstarch and glycerol. The oregano essential oil obtain the raw material used was the variety Italian Oregano or Origanum majorana using a Clevenger-type apparatus. The study included the refractive index, chemical composition, color at day 0 and day 10 and antimicrobial activity of Salmonella Enteritidis and Escherichia Coli O157:H7. The films were prepared according to the method of casting, cornstarch, glycerol (plasticizer) and water. To assess the effect of the composition on the physical properties of films, the experiment was arranged in a 22 factorial design, with one central point. It analyzed the transfer of water vapor (Method ASTM E96-92) and color. The film which showed the best characteristics was selected; subsequently oregano essential oil was added. The refractive index of the oregano essential oils obtained from the various extractions varied between 1.4875 and 1.4981. There was a significant difference (P<0.05) between the parameters a* and b* between day 0 and day 10. According to gas chromatography analysis, 52 compounds were identified in oregano essential oil, thymol (31.96%) and carvacrol (0.66%) phenols. The test antimicrobial activity, showed that Salmonella Enteritidis and Escherichia Coli O157:H7 were extremely sensitive to pure essential oil. The films obtained were transparent, presented homogeneous and compact surfaces. The values of permeability to water vapor were between 1.93 x 10-12 and 9.85 x 10-12 (g/m.s.Pa). The Analysis of Variance (ANOVA) indicated a significant differences between the different formulation (P<0.05). The incorporation of oregano essential oil at the formulations influenced the permeability presenting more or less resistant to the passage of water vapor. About the color, incorporating essential oil did not affect the appearance and did not show strong antibacterial activity at the concentration at which it was decided to work.